Bacterial membrane vesicles: orchestrators of interkingdom interactions in microbial communities for environmental adaptation and pathogenic dynamics - Xiu, Lijun; Wu, Yuwei; Lin, Gongshi; Zhang, Youyu; Huang, Lixing (Frontiers in Immunology, 2024)
Bacterial membrane vesicles (MVs) have attracted increasing attention due to their significant roles in bacterial physiology and pathogenic processes. In this review, we provide an overview of the importance and current research status of MVs in regulating bacterial physiology and pathogenic processes, as well as their crucial roles in environmental adaptation and pathogenic infections. We describe the formation mechanism, composition, structure, and functions of MVs, and discuss the various roles of MVs in bacterial environmental adaptation and pathogenic infections. Additionally, we analyze the limitations and challenges of MV-related research and prospect the potential applications of MVs in environmental adaptation, pathogenic mechanisms, and novel therapeutic strategies. This review emphasizes the significance of understanding and studying MVs for the development of new insights into bacterial environmental adaptation and pathogenic processes. Overall, this review contributes to our understanding of the intricate interplay between bacteria and their environment and provides valuable insights for the development of novel therapeutic strategies targeting bacterial pathogenicity.